Construction of DPI Intelligent Network System Based on SDN/NFV - Jie Pan; Zhuoning Xi; Peng Lin (Dianxin kexue)
DPI devices are widely used in a variety of analysis system of network traffic and business. It is the first step to complete the traffic identification and processing，and has been widely deployed in the network. With the development of DPI technology，the rise of administrative cost and capital cost brought by massive embedded DPI devices is also increasingly prominent. The current situation and existing problems of traditional DPI deployment scenarios were elaborated，and a more advanced intelligent network system and deployment scenarios with DPI software embedded on the basis of SDN/NFV technology were described.